Changes in Trypanosoma cruzi -Specific Immune Responses after Treatment: Surrogate Markers of Treatment Efficacy - Laucella, Susana A.; Mazliah, Damián Pérez; Bertocchi, Graciela; Alvarez, María G.; Cooley, Gretchen; Viotti, Rodolfo; Albareda, María C.; Lococo, Bruno; Postan, Miriam; Armenti, Alejandro; Tarleton, Rick L. (Clinical infectious diseases, 2009)
Background.As many as 20 million people are living with Trypanosoma cruzi infection in Latin American, yet few receive any treatment. The major limitation in developing and evaluating potential new drugs for their efficacy is the lack of reliable tests to assess parasite burden and elimination. Methods.Adults volunteers with chronic T. cruzi infection were evaluated clinically and stratified according to the Kuschnir classification. Individuals with group 0 and group 1 clinical status were treated with benznidazole (5 mg/kg per day for 30 days). The changes in T. cruzi -specific T cell and antibody responses, as well as in clinical status, were measured periodically over the 3–5-year follow-up period and were compared with pretreatment conditions and with values in an untreated control group. Results.The frequency of peripheral interferon (IFN)-γ-producing T cells specific for T. cruzi declined as early as 12 months after benznidazole treatment and subsequently became undetectable in a substantial proportion of treated subjects. In addition, decreases in antibody responses to a pool of recombinant T. cruzi proteins also decreased in many of these same subjects. The shift to negative IFN-γ T cell responses was highly associated with an early increase in IFN-γ-producing T cells with phenotypic features of effector/effector memory cells in a subset of subjects. Benznidazole treatment also resulted in an increase in naive and early differentiated memory-like CD8+T cells in a majority of subjects. Conclusions.Benznidazole treatment during chronic Chagas disease has a substantial impact on parasite-specific immune response that is likely indicative of treatment efficacy and cure.